Information war. The USA and Great Britain during World War II (1939 - 1945) - Tetiana Klynina (Cхід)
In the current development context of the political world such phenomenon as 'information war' is used by numerous states as an instrument for implementation of their foreign policy. The outset of information war can be related to the early 20th century, it was however World War II which gave an impetus to the development of information war that, subject to its purposes, acted as propaganda, counterpropaganda, psychological war etc. The paper covers an information aspect of foreign activities of theUSAandGreat Britainduring World War in respect ofGermany. It is shown that, depending on the time of the entry of one or another country into the war, there were some agencies set up, which were charged with carrying out information activity overseas. In theUSAsuch agencies were the Office of Coordination Information, the Office of War Information, the United States Information Service and others. InGreat Britainit was the Ministry of Information, which exercised the above function. The paper covers the setup process of the organizations in question and their core activities. It is indicated that when World War II had ended, the above agencies were wound up, their functions delegated to other government institutions. The paper places special emphasis on enemy disinformation operations (use of secret agents, radio broadcasting, distribution of leaflets, broadsheets and newspapers) which eventually resulted in achievement of the main goal of the allies in the war - the victory.